(untitled) (Global Journals of Research in Engineering, 2012)
The purpose of the paper is to illustrate the process of implementing Six Sigma in a cable manufacturing organization of Bangladesh Major fundamental streams have been introduced to outline the concept of Six Sigma for Bangladeshi industries and the related methodologies for the research and finally the sigma level of the organization is determined Practicing Six Sigma could enable the company to eliminate a wide range of long standing process variation problem This research had been undertaken to highlight the importance of a structured process and the importance data collection Originally it could be drawn attention to the managers on how Six Sigma can be used to enhance existing improvement efforts Finally the specific practical example shows how the approach can be used to tackle long standing and often hidden quality issues